Improved Resting-State Functional Dynamics in Post-stroke Depressive Patients After Shugan Jieyu Capsule Treatment - Yao, Guanqun; Li, Jing; Wang, Jiaojian; Liu, Sha; Li, Xinrong; Cao, Xiaohua; Chen, Huafu; Xu, Yong (Frontiers in Neuroscience, 2020)
Shugan jieyu Capsule (SG), a Chinese herbal medicine mainly composed of acanthopanax and hyperium perforatum, has been used to ameliorate cognitive impairment and emotional problems induced by post-stroke depression (PSD), while the altered dynamics of brain underlying the ameliorative effects of SG remain unclear. The present study aimed to explore the underlying neurobiological mechanisms of SG in ameliorating cognitive function of PSD using resting-state functional magnetic resonance imaging (fMRI). fMRI and cognitive assessment for 15 PSD patients underwent SG-treatment for 8 weeks and 21 age- and gender-matched healthy controls (HC) were acquired, and dynamic amplitude of low frequency fluctuations (dALFF) and functional connectivity (dFC) were used to reveal the changes of dynamic functional patterns. We found that administrating SG can significantly reduce the depressive symptom assessed with Hamilton Depression Scale (HAMD-24) and improve the cognitive functions assessed with Montreal Cognitive Assessment (MoCA). dALFF and dFC analyses revealed significant increased dALFF in altered right precuneus and decreased dFC between right precuneus and left angular gyrus in PSD patients after SG treatment, and the changed patterns in PSD patients after SG treatment were consistent with that compared to HC. Moreover, the dALFF variance in the right precuneus was positively correlated with MoCA scores in PSD patients after treatment. These findings indicate that SG may improve post-stroke depression patients’ cognitive function through altered brain dynamics. These results provide a foundation for future studies of the potential physiological mechanism of SG.